Evaluation and treatment physiotherapeutic in pain syndrome patellofemoral: case study - Santos, Keyla Mara dos; Martins, Tamiris Bepler; Abou, Libak; Palandi, Juliete; Venâncio, Raysa Silva; Moreira, Géssica Maria (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
Introduction: The patellofemoral pain syndrome is a common condition in orthopedic practice, is defined as a pain or retropatellar in the absence of other diseases of the knee, multifactorial. Objectives: The aim of this study was to investigate the influence of a physiotherapy intervention in a patient with patellofemoral pain syndrome. Methods: We performed a descriptive study, through a case report with physical therapy assessment data and the description of the techniques used during treatment. Results: The results showed range of motion improves, the manifestations of pain and patellar mobility. Conclusion: The proposed physical therapy treatment given to this patient proved to be efficient, but a greater number of physical therapy sessions is required in order to obtain better results.